2017
DOI: 10.1080/16549716.2017.1320118
|View full text |Cite
|
Sign up to set email alerts
|

Thinking about the environment and theorising change: how could Life History Strategy Theory inform mHealth interventions in low- and middle-income countries?

Abstract: Background: There is a growing body of literature outlining the promise of mobile information and communication technologies to improve healthcare in resource-constrained contexts.Methods: We reviewed the literature related to mobile information and communication technologies which aim to improve healthcare in resource-constrained contexts, in order to glean general observations regarding the state of mHealth in high-income countries (HIC) and low- and middle-income countries (LMIC).Results: mHealth interventi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 45 publications
(64 reference statements)
0
9
0
Order By: Relevance
“…Another review found that IMB was the most common theory employed in eHealth interventions targeting medication adherence [46]. The use of theory was less common among studies in low- and middle-income countries (LMIC;19%) relative to high-income countries (HIC; 48%) [3,23]. The lack of theory-informed eHealth interventions is not unique to the field of HIV prevention and treatment.…”
Section: How Well Does Ehealth Intervention Research Incorporate Healmentioning
confidence: 99%
“…Another review found that IMB was the most common theory employed in eHealth interventions targeting medication adherence [46]. The use of theory was less common among studies in low- and middle-income countries (LMIC;19%) relative to high-income countries (HIC; 48%) [3,23]. The lack of theory-informed eHealth interventions is not unique to the field of HIV prevention and treatment.…”
Section: How Well Does Ehealth Intervention Research Incorporate Healmentioning
confidence: 99%
“…Although users may briefly accommodate the innovation, they will be less invested in making long-term commitments requiring individual and organizational realignment, for short-term gains. In addition to being user-centered and accounting for the context, it is imperative that multiple stakeholder perspectives are leveraged during innovation design [6,7,35]. High-ranking supervisors might seem distant from the usage process but could compel or foster accountability and usage.…”
Section: Discussionmentioning
confidence: 99%
“…However, such work should be approached with caution. Indeed, the potential of mHealth, as has been widely proposed (Chang et al, 2011;Chib et al, 2015;Morgan et al, 2017), could lie in its capacity to reach underserved populations (although current analyses have cast some doubt on this, see Jennings and Gagliardi, 2013;Morgan et al, 2017). Resource constraints are endemic in many low-and middle-income countries and hinder public health efforts.…”
Section: Ai Big Data and Mhealth: Closing Or Widening Inequalitiesmentioning
confidence: 99%
“…Resource constraints are endemic in many low- and middle-income countries and hinder public health efforts. A substantial number of mHealth interventions have thus been implemented in LMIC public health in the past decade, premised on the assumption that such technologies can bridge the resources divide (Chang et al, 2011 ; Chib et al, 2015 ; Morgan et al, 2017 ). However, as commentators have noted, mHealth interventions alone are unlikely enough to achieve real behavior change, in contexts where economic, social, political, and infrastructural barriers to service access and behavior change are unlikely to be addressed by messaging alone (Morgan et al, 2017 ).…”
Section: Directions For Policy and Programming For Ai Big Data And mentioning
confidence: 99%
See 1 more Smart Citation